IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IIIB SD NEGERI 017 SEDINGINAN - Sri Wahyuni; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the lack of science learning outcomes of students, with a grade average of 46,66. While the completeness criteria Minimum value (KKM) IPS was 70 of 20 students only 8 people were reached with classical completeness. This research is Classroom Action Research (CAR) conducted aiming to improve student learning outcomes IPS class IIIA SD Negeri 017 Sedinginan by implementing cooperative learning model Group Investigation. Formulation of the problem: Is the application of cooperative learning model type Group Investigation can improve student learning outcomes IPS class IIIA SD Negeri 017 Sedinginan. Data collection instruments is observation activity sheets and teacher and student learning outcomes. The results of observations of teacher activity in the learning process at the first meeting of the first cycle of 62.5% (category enough) and the second meeting increased to 75,0% (both categories), the first meeting of the second cycle of 87,5% (excellent category) and the second meeting increased to 95,83% (excellent katergori). The results of observations of student activity in the first cycle the first meeting of 58,33% (sufficient category) and the second meeting increased to 70,83% (both categories), the first meeting of the second cycle of 83,33% (excellent category) and the second meeting increased to 91,66 % (excellent category). Learning outcomes of the preliminary data obtained with an average of 46,66 (enough categories) increased in the first cycle with the average being 64,66 (both categories) percentage increased to 18%. In the second cycle increased by an average of 67,00 (excellent category) with an increase in the percentage of 2,34%. The results of research in the class IIIA SD Negeri 017 Sedinginan prove that the application of cooperative models Invesitgation Group can improve student learning outcomes IPS class IIIA SD Negeri 017 Sedinginan.Keywords: Models of Learning Group Investigation, Learning Outcomes ipa.